(untitled) (European Bison Conservation Newsletter, 2010)
Initially, a European bison enclosure of the Institute for Applied Ecology (IES) was planed in the village named Grabin (in the territory of the Gryżyński Landscape Park and the area of Nature 2000 “Gryżyna’s Gully” – the Lubuskie Voivodship, Krośnieński Poviat, Bytnica Commune). The place designed for the enclosure had to change, however, as the inhabitants unexpectedly came to the conclusion that they not wish to have a European bison breeding center and bison anymore. Disputes connected with the location of the enclosure in the environmentally valuable areas were reflected in numerous letters directed to, among others, the Minister of Environment and the coordinator of the European bison project, i.e. prof. Wanda Olech and in few articles placed in national newspapers. Hence, it was decided that another place must be found for European bison herd. Eventually, bison shall be placed in the village named Sycowice (Czerwieńsk Commune), only 3 km away from originally planned site. This place was proposed by the local Village Soltis, Mr Cezary Woch, for whom the building of the European bison farm is a great chance for development and promotion of Sycowice. This territory is less bountiful, but still regarded by specialists as adequate for bison. The resentment of the Grabin village inhabitants is only one of many obstacles that European bison encounter in Poland. It is comforting that among those who have certain misgivings there also the ones who value these animals and feel the need to learn their ecology and support the protection of this species. The situation which occurred in Grabin shows us all how much work is still needed to help “the King of Primeval Forest” to survive.